Mobilizing farmers to stop land degradation: A different discourse from Burundi. (4th October 2020) - Kessler, Aad; van Reemst, Laurie; Beun, Micael; Slingerland, Erik; Pol, Laura; De Winne, Ruben
Abstract: Stopping land degradation is one of the biggest challenges worldwide and particularly in Burundi, with its unprecedented rates of soil loss and growing food insecurity. This article proposes a different discourse on how to engage people in stopping land degradation, and presents results and lessons learned from a bottom‐up inclusive approach implemented since 2014 in Burundi: the integrated farm planning (PIP) approach. The PIP approach aims to build a solid foundation for sustainable change toward enhanced food production and good land stewardship, based on three foundation principles (motivation, stewardship, and resilience) and three guiding principles (empowerment, integration, and collaboration). This article is based on two studies undertaken in 2018: an impact study among 202 households and a qualitative study using the most significant change methodology with 30 households. Findings from both studies provide initial support that the PIP approach generates considerable changes at household, farm, and village level. Based on a vision and a plan for their farm, motivated PIP households are currently investing in the resilience of their farms and applying a diversity of conservation practices, while in all PIP villages concrete collective action is undertaken for sustainable land stewardship. Given its rapid upscaling in Burundi and the potential of the PIP approach to mobilize farmers for motivated action, the article concludes with a reflection on the core elements of a different discourse to stop land degradation.